Lipopolysaccharide-induced interleukin 8 production by human whole blood is enhanced by epinephrine and inhibited by hydrocortisone. - van der Poll, T (1997)
To determine the effect of epinephrine and hydrocortisone on lipopolysaccharide (LPS)-induced interleukin 8 (IL-8) production, human whole blood was stimulated with LPS in the presence or absence of these stress hormones. Epinephrine caused a dose-dependent increase in LPS-induced IL-8 production, which was mediated exclusively via beta-adrenergic receptors, as reflected by the facts that beta (but not alpha) receptor blockade reversed the epinephrine effect and beta (but not alpha) receptor stimulation reproduced the epinephrine effect. Further, elevating cellular cyclic AMP (cAMP) concentrations, a known effect of beta-adrenergic stimulation, by addition of dibutyryl cAMP also enhanced LPS-induced IL-8 production. Epinephrine-induced upregulation of IL-10 production masked an even more pronounced stimulating effect of this hormone on IL-8 synthesis, as indicated by the finding that the extent of IL-8 upregulation was greater in the presence of anti-IL-10 than in the absence of anti-IL-10. Hydrocortisone dose-dependently inhibited LPS-induced IL-8 production and reversed epinephrine-induced enhancement of IL-8 production. Epinephrine and hydrocortisone have opposite effects on IL-8 production, which may be relevant for the understanding of endogenous and therapeutic stress hormone influences on IL-8 mediated inflammation.